Capitalist dynamics fictional expectations and the openness of the future - Jens Beckert (Max Planck Institute for the Study of Societies, 2014)
Capitalism is an economic and social order oriented toward the future. In this paper, I describe the unfolding of the temporal order of capitalism and relate it to the restless dynamism of capitalism we have observed since the Industrial Revolution. Since the future is open, actors are confronted with the uncertainty of the outcomes of their decisions. What can expectations be under conditions of uncertainty? To answer this question, I introduce the notion of fictional expectations which can be used to describe decisions made under conditions of an open and uncertain future. In the paper's penultimate section, I apply the concept of fictional expectations to the analysis of four crucial processes of capitalism: money and credit, investments, innovation, and consumption. The main thrust of the paper is that in order to understand economic action in capitalism, actors' perceptions of the future need to take center stage. Not only history matters, but also the future matters. – – Der Kapitalismus als wirtschaftliche und soziale Ordnung orientiert sich an der Zukunft. In diesem Artikel beschreibe ich die Entwicklung der zeitlichen Ordnung des Kapitalismus und setze sie zu dem unaufhaltsamen wirtschaftlichen Wandel seit der industriellen Revolution in Beziehung. Da die Zukunft offen ist, sind Akteure mit der Ungewissheit von Handlungsresultaten konfrontiert. Was sind Erwartungen unter Bedingungen von Ungewissheit? Zur Beantwortung dieser Frage führe ich das Konzept der fiktionalen Erwartungen ein, mit dem sich Entscheidungen unter Bedingungen einer offenen und ungewissen Zukunft beschreiben lassen. Im vorletzten Teil nutze ich das Konzept der fiktionalen Erwartungen zur Untersuchung von vier zentralen Aspekten kapitalistischer Wirtschaft: Geld und Kredit, Investitionen, Innovationen und Konsum. Die wichtigste Überlegung der Ausführungen ist, dass die Analyse wirtschaftlichen Handelns im Kapitalismus die Berücksichtigung der Wahrnehmung der Zukunft verlangt. Nicht nur history matters, sondern die Zukunft ist ebenso wichtig.
Keywords: 300